¿Construyendo una masculinidad «alternativa» desde la escuela peruana? Una aproximación a la socialización masculina del joven en un colegio limeño de orientación alternativa - Rondán Vásquez, Luis (2015)
This research seeks to show the ways of male social performance by students in educational environments in which they are more likely to question the traditional model of masculinity (TMM) that characterizes the man as a different and superior being than the woman. As a way to approach to that phenomena, we have decided to study a private, secular, mixed and «alternative» school (characterized by promoting democratic values), because previous research showed evidence that these schools actively challenge gender stereotypes. We found that the male performance of the students reproduces, at the very least partially, the TMM model. The measures used by the school to promote gender equality were useful to promote practices that took distance from some TMM issues (suchas emotional expressiveness) but are not sufficient to ensure that other aspects of TMM will not be reproduced (such as the tendency of male domination or gay rejection).